Method for manufacturing phosphoric acid-based composite conductive particles coated with a dopamine layer and a pvdf layer

CN122907570APending Publication Date: 2026-10-13SHENZHEN TXD TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610862685.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-06-17
Filing Date
2026-06-15
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

这会导致正极颗粒与正极浆料劣化,进而增加制程工艺的难度,且制作出的正极极板的电化学性质容易不如预期

Benefits of technology

[0006]本发明要解决的技术问题是:提出一种制造包覆有多巴胺层及PVDF层的磷酸类复合助导颗粒的方法,是在原本包覆有多巴胺层的陶瓷颗粒外表面再包覆一层PVDF层作为保护层,使得PVDF层能够进一步保护内部的二级复合颗粒,从而避免其与正极浆料内的溶剂发生反应导致正极浆料劣化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907570A_ABST
    Figure CN122907570A_ABST
Patent Text Reader

Abstract

The application discloses a method for manufacturing phosphoric acid composite conductive particles coated with a dopamine layer and a PVDF layer, which comprises the following steps: step 500: a plurality of composite ceramic particles are mixed with a first alcohol solution to form a first mixed slurry; each composite ceramic particle is composed of a particle ceramic coated with a dopamine layer on the outer surface; step 510: a mixed solution of PVDF, a second alcohol solution and NMP is mixed to form a second mixed slurry; step 520: the first mixed slurry and the second mixed slurry are mixed to form a third mixed slurry; the PVDF forms a PVDF layer to coat the outer surface of the composite ceramic particle; step 530: the third mixed slurry is grinded to form a third mixed slurry with higher flowability; and step 540: the third mixed slurry with higher flowability is dried to obtain a plurality of composite conductive particle powders.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery cathode technology, and in particular to a method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer. Background Technology

[0002] A battery mainly consists of a positive electrode and a negative electrode placed in an electrolyte. In traditional technology, ceramic particles are added to the negative electrode to increase ionic conductivity. Because ceramic particles have high ionic conductivity for lithium ions, when lithium ions pass through the negative electrode, the dispersed ceramic particles can guide the lithium ions, thereby dispersing the transport path of the lithium ions and resulting in a uniform channel distribution of lithium ions inside the positive electrode.

[0003] Traditional ceramic particles have a large number of alkaline groups (such as OH-, Li2O) on their surface. Therefore, during the manufacturing process, when multiple traditional ceramic particles are added to the positive electrode slurry, these alkaline groups react with the solvent in the slurry, making the slurry highly alkaline. This leads to the degradation of both the positive electrode particles and the slurry, increasing the difficulty of the manufacturing process and making the electrochemical properties of the produced positive electrode plate less than expected. While existing technologies include coating traditional ceramic particles with a dopamine layer to protect them, the dopamine layer cannot completely cover the outer surface of the ceramic particles, leaving a small portion of the particle surface exposed.

[0004] Therefore, this case aims to propose a novel method for manufacturing phosphate-based composite conductive particles coated with dopamine and PVDF layers to overcome the deficiencies in the prior art.

[0005] Therefore, existing technologies have shortcomings and need to be improved. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to propose a method for manufacturing phosphoric acid composite conductive particles coated with a dopamine layer and a PVDF layer. The method involves coating the outer surface of ceramic particles originally coated with a dopamine layer with a PVDF layer as a protective layer. This allows the PVDF layer to further protect the internal secondary composite particles, thereby preventing them from reacting with the solvent in the positive electrode slurry and causing the positive electrode slurry to deteriorate.

[0007] The technical solution of this invention is as follows: A method for manufacturing phosphoric acid composite conductive particles coated with a dopamine layer and a PVDF layer is proposed, wherein the composite conductive particles are disposed within a slurry layer of an electrode; the method includes the following steps: Step 500: Take multiple composite ceramic particles and the first alcohol solution and put them into a first mixer to mix them to form a first mixed slurry; Each composite ceramic particle is composed of ceramic particles coated with a layer of dopamine on the outer surface; The dopamine layer is composed of polydopamine molecules; The dopamine layer cannot completely cover the outer surface of the ceramic particles, so a small portion of the ceramic particles will still be exposed. The ceramic particles have high ionic conductivity for lithium ions. These ceramic particles are used to guide and disperse lithium ions, preventing abnormal accumulation of lithium ions in the electrode slurry and avoiding side reactions with the electrode slurry.

[0008] Step 510: Take a mixed solution of PVDF, the second alcohol solution and NMP and put it into a second mixer to mix them to form a second mixed slurry; Step 520: The first and second mixed slurries are placed in an emulsifier for mixing to form a third mixed slurry. At this time, multiple composite ceramic particles in the first mixed slurry react with PVDF in the second mixed slurry. Some of the fluoride ions in the PVDF form ionic bonds with the lithium ions on the surface of the corresponding ceramic particles to form lithium fluoride. Other fluoride ions in the PVDF form hydrogen bonds with the nitrogen ions in the dopamine layer on the surface of the composite ceramic particles. Therefore, PVDF forms a PVDF layer that coats the outer surface of the composite ceramic particles. The PVDF layer and the corresponding composite ceramic particles form composite conductive particles. In this step, PVDF and composite ceramic particles form multiple aggregates due to their chemical properties, causing the third mixed slurry to gel and become a giant structure. Step 530: The gelled third mixed slurry is placed in a grinding mill for grinding to form a highly fluid third mixed slurry. That is, the multiple aggregates formed by the multiple composite ceramic particles and PVDF in the gelled third mixed slurry are ground into stable and fine particles. After physical and mechanical grinding by the grinding mill, the giant structure can be destroyed, so that the originally agglomerated PVDF becomes fine PVDF fragments, which still have the original properties of PVDF. The PVDF fragments fill the exposed places of ceramic particles. Therefore, this grinding step makes the composite conductive particles more stable and finer, thus forming a highly fluid third mixed slurry. Step 540: The highly fluid third mixed slurry is placed in a vacuum thickener for drying to remove the first alcohol solution, the second alcohol solution and NMP in the third mixed slurry, and to obtain a powder composed of composite guiding particles.

[0009] The following explanation will provide a further understanding of the features and advantages of this work. Please refer to the accompanying illustrations while reading. Attached Figure Description

[0010] Figure 1 This is a schematic diagram of the process steps of the present invention.

[0011] Figure 2This is a flowchart illustrating the operation of the present invention.

[0012] Figure 3 This is a schematic cross-sectional view of the structure of the present invention.

[0013] Figure 4 This is a schematic diagram illustrating an application example of the present invention. Detailed Implementation

[0014] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments.

[0015] Please refer to Figures 1 to 4 The diagram illustrates a method for manufacturing phosphoric acid-based composite conductive particles coated with a dopamine layer and a PVDF layer according to the present invention. The composite conductive particles 100 are primarily used in the electrode 10 of a solid-state or near-solid-state battery. Multiple composite conductive particles 100 can be disposed within the electrode 10, which is particularly the positive electrode of a solid-state or near-solid-state battery. The particle size of the composite conductive particles 100 is less than 300 nanometers. The electrode 10 includes: Electrode substrate 11 is a material used as a carrier plate to support electrode 10. An electrode paste layer 13 is coated on an electrode substrate 11. The electrode paste layer 13 includes an electrode paste 12 as a binder and also includes a plurality of composite conductive particles 100.

[0016] The weight percentage of multiple composite conductive particles 100 in the electrode slurry layer 13 ranges from 2 wt% to 10 wt%.

[0017] The method for manufacturing the composite conductive particles 100 according to the present invention is as follows: Figure 1 As shown, it includes the following steps: Step 500: Multiple composite ceramic particles 110 and a first alcohol solution 111 are placed in a first mixer 600 and mixed to form a first slurry 120. Each composite ceramic particle 110 is composed of ceramic particles 15 coated with a dopamine layer 35. This dopamine layer 35 is composed of polydopamine molecules. The bonding mechanism between the polydopamine molecules and the ceramic particles 15 is well known to those skilled in the art and will not be described in detail here. For example, the ceramic particles 15 are bonded to OH groups via external hydrogen bonds. - The bond between the OH group in dopamine - The bonds are formed through a dehydration polymerization reaction. The ceramic particles 15 have a particle size of less than 100 nanometers; the thickness of the dopamine layer 35 is between 2 nanometers and 15 nanometers. The dopamine layer 35 cannot completely cover the outer surface of the ceramic particles 15, so a small portion of the surface of the ceramic particles 15 remains exposed.

[0018] The first alcohol solution 111 is selected from methanol, ethanol, and isopropanol, etc. The total weight of the composite ceramic particles 110 as a percentage (i.e., solid content) of the first mixed slurry 120 is between 5 wt% and 10 wt%, preferably 9 wt%.

[0019] The ceramic particles 15 have high ionic conductivity for lithium ions. Therefore, when lithium ions pass through the electrode 10, the ceramic particles 15 guide and disperse the lithium ions, so that a uniformly distributed lithium ion channel can be formed within the electrode 10, avoiding abnormal accumulation of lithium ions in the electrode slurry 12 and side reactions with the electrode slurry 12.

[0020] Ceramic particles 15 have lithium-ion conductivity (ionic conductivity greater than 10). -5 Ceramic oxides with a diffusion coefficient of cm² / s (cm² / s). Among them, ceramic oxides with lithium-ion conductivity include, for example, lithium aluminum germanium phosphate (LAGP) with a NASICON (sodium superionic conductor) structure.

[0021] When ceramic particles 15 are composed of LAGP, the LAGP is selected from Li 1+x Al x Ge 2-x (PO4)3, or Li 1+x+y Al x Ge 2-x-y-z M y N z (PO4)3, where x is between 0.1 and 0.8, y is between 0 and 0.2, and z is between 0 and 0.2. M is a trivalent cation, such as Sc. 3+ (scandium ion), Y 3+ (Yttrium ions), Ga 3+ (Gallium ions), In 3+ (Indium ion), La 3+ (Lanium ion), etc.; where N is a tetravalent cation, such as Zr. 4+ (Zirconium ion), Si 4+ (Silicon ions), Sn 4+ (Tin ions), etc.

[0022] Step 510: Take 40g of PVDF (polyvinylidene difluoride), 112g of the second alcohol solution and NMP (N-methylpyrrolidone) mixture and mix them in the second mixer 610 to form a second mixed slurry 130. The second alcohol solution is selected from methanol, ethanol, and isopropanol, etc. The first alcohol solution 111 and the second alcohol solution can be selected from the same alcohol solution. In the mixed solution 112, the weight ratio of the second alcohol solution to NMP is 0.85:0.15.

[0023] The PVDF 40 accounts for a weight percentage (i.e., solid content) of the second mixed slurry 130 between 0.5 wt% and 0.8 wt%. The total weight ratio of PVDF 40 to the total weight of the composite ceramic particles 110 is 1:50.

[0024] Step 520: The first mixed slurry 120 and the second mixed slurry 130 are placed into the emulsifier 620 for mixing to form a third mixed slurry 140. At this time, multiple composite ceramic particles 110 in the first mixed slurry 120 will react with PVDF 40 in the second mixed slurry 130, and some of the fluoride ions (F ions) in PVDF 40 will react with the PVDF 40. - ) will react with lithium ions (Li) on the surface of the corresponding ceramic particles 15 + The fluoride ions in PVDF 40 form ionic bonds, resulting in lithium fluoride (LiF); while the other part of PVDF 40 contains fluoride ions (F... - ) will react with nitrogen ions (N) in the dopamine layer 35 on the surface of the composite ceramic particles 110. - Hydrogen bonds are formed. Therefore, PVDF 40 will form a PVDF layer 41 coating the outer surface of the composite ceramic particles 110, and the PVDF layer 41 and the corresponding composite ceramic particles 110 form composite conductive particles 100 (such as...). Figure 3 (As shown). In this step, PVDF 40 and composite ceramic particles 110 will form multiple agglomerates due to their chemical properties, causing the third mixed slurry 140 to curing into a giant structure.

[0025] In step 520, the mixing time is 30 minutes to 1 hour. The thickness of the PVDF layer 41 is between 10 nanometers and 100 nanometers.

[0026] The purpose of coating with PVDF layer 41 is because solvents are present during the manufacturing process of electrode paste 12, and ceramic particles 15 are hydrophilic. Although the outer surface of ceramic particles 15 is coated with dopamine layer 35, the dopamine layer 35 cannot completely cover the outer surface of ceramic particles 15, so a small portion of the surface of ceramic particles 15 remains exposed. The exposed surface has a large number of basic groups (such as OH groups). -(Li₂O). When multiple composite ceramic particles 110 are added to the positive electrode slurry, the alkaline groups of the composite ceramic particles 110 react with the solvent in the positive electrode slurry, making the positive electrode slurry strongly alkaline. This leads to the degradation of the positive electrode particles and the positive electrode slurry, thereby increasing the difficulty of the manufacturing process, and the electrochemical properties of the produced positive electrode plate are likely to be worse than expected. Therefore, by coating the dopamine layer 35 with a PVDF layer 41, the reaction between the ceramic particles 15 and the solvent in the electrode slurry 12 can be completely isolated, thereby improving battery performance.

[0027] Step 530: The gelled third mixed slurry 140 is placed in a grinder 630 for grinding to form a highly fluid third mixed slurry 140. This involves grinding the multiple agglomerates formed by the composite ceramic particles 110 and PVDF 40 in the gelled third mixed slurry 140 into stable, fine particles. The physical and mechanical grinding in the grinder 630 breaks down the large structures, causing the originally agglomerated PVDF 40 to revert to fine PVDF fragments. These fragments retain the original properties of PVDF and can fill the exposed areas of the ceramic particles 15. Therefore, this grinding step makes the composite guiding particles 100 more stable and finer, while also promoting the completion of the reaction. The particle size of the composite guiding particles 100 is less than 300 nanometers, thus forming a highly fluid third mixed slurry 140. The grinding time in step 530 is 1.5 to 2 hours.

[0028] Step 540: The highly fluid third mixed slurry 140 is placed into a vacuum thickener 640 for drying to remove the first alcohol solution 111, the second alcohol solution and NMP in the third mixed slurry 140, thereby obtaining a powder composed of composite guiding particles 100.

[0029] The advantage of this invention is that a PVDF layer is coated on the outer surface of the ceramic particles that are originally coated with a dopamine layer as a protective layer. This allows the PVDF layer to further protect the internal secondary composite particles, thereby preventing them from reacting with the solvent in the positive electrode slurry and causing the positive electrode slurry to deteriorate.

[0030] The above detailed description is a specific illustration of a feasible embodiment of the present invention, but this embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementations or modifications that do not depart from the spirit of the present invention should be included within the patent scope of the present invention.

Claims

1. A method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer, characterized in that, The composite conductive particles are disposed within the slurry layer of an electrode; the method includes the following steps: Step 500: Take multiple composite ceramic particles and the first alcohol solution and put them into the first mixer to mix them to form a first mixed slurry; each composite ceramic particle is composed of ceramic particles coated with a dopamine layer on the outer surface; the dopamine layer is composed of polydopamine molecules; wherein the dopamine layer cannot completely cover the outer surface of the ceramic particles, so a small portion of the surface of the ceramic particles will still be exposed; The ceramic particles have high ionic conductivity for lithium ions; the ceramic particles are used to guide and disperse lithium ions, preventing abnormal accumulation of lithium ions in the electrode slurry and side reactions with the electrode slurry. Step 510: Take a mixed solution of PVDF, the second alcohol solution and NMP and put it into the second mixer to mix and form a second mixed slurry; Step 520: The first and second mixed slurries are placed in an emulsifier for mixing to form a third mixed slurry. At this time, multiple composite ceramic particles in the first mixed slurry react with PVDF in the second mixed slurry. Some of the fluoride ions in PVDF form ionic bonds with the lithium ions on the surface of the corresponding ceramic particles to form lithium fluoride. Other fluoride ions in PVDF form hydrogen bonds with the nitrogen ions in the dopamine layer on the surface of the composite ceramic particles. Therefore, PVDF forms a PVDF layer that coats the outer surface of the composite ceramic particles. The PVDF layer and the corresponding composite ceramic particles form composite conductive particles. In this step, PVDF and composite ceramic particles form multiple aggregates due to their chemical properties, causing the third mixed slurry to gel and become a giant structure. Step 530: Place the gelled third mixed slurry into a grinder for grinding to form a third mixed slurry with high fluidity, that is, grind the multiple agglomerates formed by multiple composite ceramic particles and PVDF in the gelled third mixed slurry into stable and fine particles. After physical and mechanical grinding by the grinding machine, the giant structure can be destroyed, and the originally agglomerated PVDF can be turned back into fine PVDF fragments. These fragments still have the original properties of PVDF and fill the exposed places of ceramic particles. Therefore, this grinding step makes the composite conductive particles more stable and finer, thus forming a third mixed slurry with higher fluidity. Step 540: The highly fluid third mixed slurry is placed into a vacuum thickener for drying to remove the first alcohol solution, the second alcohol solution and NMP in the third mixed slurry, thereby obtaining a powder composed of composite guiding particles. The ceramic particles are ceramic oxides with lithium-ion conductivity, wherein the lithium-ion conductivity refers to a diffusion coefficient related to ionic conductivity greater than 10. -5 cm 2 / s.

2. The method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer according to claim 1, characterized in that, The ceramic particles are smaller than 100 nanometers; the thickness of the dopamine layer is between 2 nanometers and 15 nanometers; the total weight of the composite ceramic particles accounts for between 5 wt% and 10 wt% of the first mixed slurry.

3. The method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer according to claim 1, characterized in that, The first alcohol solution is selected from one or a combination of at least two of methanol, ethanol, and isopropanol; the second alcohol solution is selected from one or a combination of at least two of methanol, ethanol, and isopropanol.

4. The method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer according to claim 1, characterized in that, The ceramic oxide with lithium-ion conductivity is lithium aluminum germanium phosphate with a NASICON structure, abbreviated as LAGP.

5. The method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer according to claim 4, characterized in that, When the ceramic particles are composed of LAGP, the LAGP is selected from Li 1+x Al x Ge 2-x (PO4)3, or Li1 +x+ y Al x Ge 2-x-y-z M y N z (PO4)3, where x is between 0.1 and 0.8, y is between 0 and 0.2, and z is between 0 and 0.2; where M is a trivalent cation and N is a tetravalent cation.

6. The method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer according to claim 5, characterized in that, The trivalent cation is selected from at least one or a combination of at least two of scandium ions, yttrium ions, gallium ions, indium ions, and lanthanum ions.

7. The method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer according to claim 5, characterized in that, The tetravalent cation is selected from one or a combination of at least two of zirconium ions, silicon ions, and tin ions.

8. The method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer according to claim 1, characterized in that, The weight ratio of the second alcohol solution to NMP is 0.85:0.15; the weight percentage of PVDF in the second mixed slurry is between 0.5 wt% and 0.8 wt%; the weight ratio of the total weight of PVDF to the total weight of the composite ceramic particles is 1:

50.

9. The method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer according to claim 1, characterized in that, In step 520, the mixing time is 30 minutes to 1 hour; the thickness of the PVDF layer is between 10 nanometers and 100 nanometers.

10. The method for manufacturing phosphate-based composite conductive particles coated with a dopamine layer and a PVDF layer according to claim 1, characterized in that, In step 530, the particle size of the composite guiding particle 100 is less than 300 nanometers; the grinding time in step 530 is 1.5 hours to 2 hours.